МОДАЛЬНЫЕ ХАРАКТЕРИСТИКИ СЕМАНТИЧЕСКОЙ СТРУКТУРЫ БЕЗЛИЧНЫХ ПРЕДЛОЖЕНИЙ В ЧЕШСКОМ ЯЗЫКЕ - Калениченко, Мария (Acta Neophilologica, 2015)
This article is devoted to the analysis of sentence modality. Modality is interpreted as a constructive element of the sentence in any function. The main attention is paid to the analysis of the semantic features that compose the complex and multi-layered representation of modality.